Influence of Tactical and Situational Variables on Offensive Sequences During Elite European Handball Matches - Ferrari, Willian; Sarmento, Hugo; Marques, Adilson; Dias, Gonçalo; Sousa, Tiago; Sánchez-Miguel, Pedro Antonio; Gama, José; Vaz, Vasco (Frontiers in Psychology, 2022)
The main objective of this study was to analyse the influence of tactical and situational variables on offensive sequences during elite European handball matches. A sample of 55 games and 5.857 offensive sequences from the European Handball Federation Champions League were analyzed using X2 and logistic regression analyses. Results indicated that positional attacks (odds ratio [OR] = 0.34; 95% CI: 0.28–0.42; p<0.001) and fast attacks (OR = 0.46; 95% CI: 0.36–0.57; p<0.001) decreased the probability of success for an offensive sequence by 66% and 54% when compared with counterattacks. Offensive sequences that start in the attacking zone seem to be less effective (~78%) than those that start from a situation of “ball in center.” Additionally, offensive sequences that finished in the defensive zone of the observed team were 3.19 times more effective than those that ended before the 9m zone. We concluded that compared with offensive sequences where the shot is performed from the 9m zone, the chances of an offensive sequence ending successfully are 3.65, 3.60, 2.21 times higher, for offensive sequences where the shot is performed from 9m, 6m, and the defensive zone, respectively. On the other hand, many variables seem to impact the performance of handball teams. Nevertheless, a significant challenge remains, and more research needs to be conducted to analyze the obstacles that teams need to overcome while attacking in the most effective way possible. This study provides practical implications to coaches, players and sports scientists in designing specific training situations that improve the effectiveness of the offensive process in handball matches.